ANALYSIS OF CYBERSECURITY REGULATIONS IN ADDRESSING HACKING ACTIVITIES IN THE DIGITAL ERA BASED ON JUSTICE VALUE - Maaliki, Naavi'u Emal (fakultas hukum universitas PGRI Semarang, 2024)
The rapid advancement of information technology in the digital era has led to a significant increase in cybercrime in Indonesia. Among the most prominent forms of cybercrime is hacking, which poses a serious challenge to law enforcement due to limitations in human resources and the country's cybersecurity infrastructure. While the ITE Law and the Personal Data Protection Law provide a foundational legal framework to combat cybercrime, these regulations require continuous updates to keep pace with the rapidly evolving nature of digital threats. Furthermore, the vulnerability of the small business sector, stemming from a lack of technological sophistication and public awareness, further exacerbates the risks. To address these challenges effectively, a comprehensive approach is required, involving collaboration between government institutions, law enforcement agencies, the private sector, and the community. This article utilizes the normative legal method, focusing on the analysis of existing written regulations and secondary data from literature. The study concludes that an integrated and coordinated effort is necessary to enhance Indonesia's cyber resilience, including the strengthening of policies, improvement of cybersecurity infrastructure, and raising public awareness. Only through such measures can Indonesia effectively mitigate the growing threats in the digital era